Updated overview on interplay between physical exercise, neurotrophins, and cognitive function in humans - Lippi, Giuseppe (J Sport Health Sci, 2020)
The many important benefits of physical exercise also encompass maintenance or improvement of cognitive functions. Among the various mechanisms underlying the association between physical exercise and brain health, recent evidence attests that neurotrophin receptor signaling may have an important role, because the activation of this pathway leads to growth and differentiation of new neurons and synapses, supports axonal and dendritic growth, fosters synaptic plasticity, and preserves survival of existing neurons. In this review of published evidence, we highlight that a positive relationship exists between physical exercise and circulating brain-derived neurotrophic factor levels and that the postexercise variation of this molecule is associated with improvement of neurocognitive functioning. Less clear evidence has instead been published for other neurotrophins, such as nerve growth factor, neurotrophin-3, and neurotrophin-4. Overall, promotion of adequate volumes and intensities of physical exercise (i.e., approximately 3 months of moderate-intensity aerobic exercise, with 2–3 sessions/week lasting not less than 30 min) may hence be regarded as an inexpensive and safe strategy for boosting brain-derived neurotrophic factor release, thus preserving or restoring cognitive functions.